Perceptions and experiences of mental health support for ambulance employees - Johnston, S; Wild, J; Sanderson, K; Kent, B (Mark Allen Healthcare, 2022)
Background: Mental ill health among ambulance staff is widespread. Evidence suggests that, with the right support, employees experiencing mental ill health can continue to work, symptom severity can be reduced and suicide prevented.